CROSS-SECTOR PARTNERSHIP IN THE ACTIVITIES OF HEALTHCARE INSTITUTIONS OF UKRAINE UNDER WARTIME CONDITIONS (INNOVATIVE ECONOMY, 2025)
Kudym O.V. CROSS-SECTOR PARTNERSHIP IN THE ACTIVITIES OF HEALTHCARE INSTITUTIONS OF UKRAINE UNDER WARTIME CONDITIONSPurpose. The aim of the article is to summarize the state and characteristics of cross-sectoral partnerships in the activities of Ukrainian healthcare institutions in wartime, as well as to analyze typical programs and initiatives involving international organizations and local partners.Methodology of research. The study uses a combination of general scientific and special methods: normative analysis of the legislative framework in the field of healthcare and public-private partnerships; content analysis of official reports and publications of international organizations (WHO, UNICEF, UNFPA, UNDP), open data from the Ministry of Health of Ukraine and the National Health Service of Ukraine; generalization of the practice of implementing partnership projects in the regions of Ukraine; elements of comparative analysis of scientific sources on the issues of cross-sectoral interaction and reform of the healthcare system.Findings. It has been substantiated that full-scale war has exacerbated the structural problems of the Ukrainian healthcare system and highlighted the need for intersectoral partnership as a mechanism for ensuring its sustainability. Key areas of cooperation have been identified: providing medical facilities with equipment and medicines, restoring infrastructure, developing mobile medical services for IDPs, integrating mental health services into primary care, and expanding rehabilitation programs with the participation of community and veteran organizations. It has been proven that interaction between state, municipal, international, public, and business structures allows for the maintenance of the functional capacity of healthcare facilities in conditions of military challenges.Originality. A systematization of forms and mechanisms of intersectoral partnership in conditions of martial law has been developed, which, unlike existing approaches, makes it possible to comprehensively define its role as an institutional tool for increasing the resilience of medical institutions. A conceptual vision of cross-sectoral interaction has been substantiated through the integration of humanitarian, restorative, and strategic components of healthcare system development, which allows for the formation of a comprehensive model of its functioning in crisis conditions. The theoretical position on strengthening the institutional capacity of the healthcare system based on partnership between different sectors has been further developed.Practical value. The results obtained can be used by state and local authorities in shaping health care development policy, by heads of medical institutions in developing models of partnership interaction, and in the process of planning the post-war reconstruction of Ukraine's health care system based on sustainability, integration, and community needs.Key words: cross-sector partnership, public-private partnership, healthcare institutions, resilience of the healthcare system, international organizations.
Keywords: cross-sector partnership; public-private partnership; healthcare institutions; resilience of the healthcare system; international organizations